For one more year with you: changes in compulsory schooling, education and the distribution of wages in Europe - Giorgio Brunello; Margherita Fort; Guglielmo Weber (Institute for the Study of Labor (IZA), 2007)
Using data from 12 European countries and the variation across countries and over time in the changes of minimum school leaving age, we study the effects of the quantity of education on the distribution of earnings. We find that compulsory school reforms significantly affect educational attainment, especially among individuals belonging to the lowest quantile of the distribution of ability. Contrary to previous findings in the relevant literature, we find that additional education reduces wage inequality below median income and increases it above median income. There is also evidence in our data that education and ability are complements in the production of human capital and earnings. While these results support an elitist education policy - more education to the brightest, they also suggest that investing in the less fortunate but bright could payoff both on efficiency and on equity grounds.
Keywords: 370; Education reforms; distribution of earnings; Europe; Bildungsreform; Schulpolitik; Bildungsniveau; Einkommensverteilung; Bildungsertrag; EU-Staaten